Os efeitos sociais da terceirização de serviços e a responsabilidade social e patrimonial das empresas tomadoras de serviços - Rocha, Luiz Henrique Carvalho (2014)
This paper discusses the social effects of outsourcing services and social responsibility and equity of companies borrowing services, starting with a theoretical analysis of the phenomenon of outsourcing service, comparing it with other areas of law, with the study homeland legislation on the subject and forecasts in the ILO Conventions and the laws of some European countries. This thesis sought to investigate the main social effects of Outsourcing Services in Brazil and the economic and financial consequences for companies that hire outsourced services. Another closely related issue that was the subject of analysis of this study deals with the use of objective liability and supportive of companies borrowing services, especially to examine the possibility that the existence of a legislation providing for these two types of liability as a solution, or at least reducing, the social effects of irreversible social-economic phenomenon